ANALISIS KEBERLANJUTAN PENGELOLAAN EKOSISTEM TERUMBU KARANG DI KAWASAN KONSERVASI LAUT DAERAH BINTAN TIMUR KEPULAUAN RIAU - ', Adriman; Purbayanto, Ari; Budiharso, Sugeng; Damar, Ario (Jurnal Perikanan dan Kelautan, 2012)
Coral reef ecosystem management in Regional Marine Conservation Area(RMCA) Bintan Timur is still a sectoral and not based on the consideration ofmulti-sectoral and multi-dimensional, so that it can cause environmental damageand social problems. The objectives of this study are: (1) to analyze the index andsustainability status of coral reef management in RMCA Bintan Timur, and (2) toanalyze the key factors for sustainable management of coral reef ecosystems.Sustainability analysis conducted by the method of Multi Dimensional Scaling(MDS) approach with Rap-Insus COREMAG techniques (Rapid Appraisal-IndexSustainability of Coral Reef Management). Analysis of key factors ofsustainability management performed a prospective analysis of the sensitivityfactors (leverage factor) of the MDS and the factors from the analysis ofstakeholders' needs. The results showed that the status of sustainability of coralreef management in RMCA Bintan Timur was quite sustainable with amultidimensional index of 55.02. There were ten key factors that influence to thesustainability, namely the condition of coral reefs, protected area, the publicrevenue, tourism employment, human resource availability, government policies,coordination among stakeholders, community compliance, environmental legalcounseling, and surveillance infrastructure.